The effect of can slim method towards stock price: evidence from consumer sector in Malaysia / Nabiha Yunos - Yunos, Nabiha (Faculty of Business and Management, 2018)
Prediction of stock price is an important thing in stock market analysis. Normally, investor make investment decision by using two analysis which is fundamental analysis that to decide when to buy and technical analysis that focusing on what to buy. It is a complex task to pick stock. Price earnings ratio, price book ratio, price sales ratio, price cash now ratio, and market capitalization are the most common criteria. When an uptrend eventually tops and the market begins to decline, it takes most stocks down with it. When the stock market is heading higher, there is no shortage of predictions about when the issue will end. That speculation is rarely accurate, and using instincts to guide the investing decisions will do more harm than good. The main purpose of this paper is to investigate the effect of CAN SLIM method towards stock price in Malaysia's consumer sector. The dependent variable of this research is stock price and this research using seven (7) independent variables which are current quarterly earnings, annual earnings, new product, new management and new high, supply and demand, leader or laggard, institutional sponsorship and market direction. The data collected from Eikon Thomson Reuters, Malaysiastock.biz and Bursa Market Place was chosen for this study from year 2012 to 2017. Furthermore, the data that had been used in this research is quantitative secondary data and the data structure is panel data. The result indicate that Institutional sponsorship and Market direction give positive and significance relationship towards the stock price.